Cosmos caudatus as a potential source of polyphenolic compounds : optimisation of oven drying conditions and characterisation of its functional properties. - Mediani, Ahmed; Abas, Faridah; Khatib, Alfi; Tan, Chin Ping (MDPI, 2013)
The aim of the study was to analyze the influence of oven thermal processing of Cosmos caudatus on the total polyphenolic content (TPC) and antioxidant capacity (DPPH) of two different solvent extracts (80% methanol, and 80% ethanol). Sonication was used to extract bioactive compounds from this herb. The results showed that the optimised conditions for the oven drying method for 80% methanol and 80% ethanol were 44.5 °C for 4 h with an IC50 of 0.045 mg/mL and 43.12 °C for 4.05 h with an IC50 of 0.055 mg/mL, respectively. The predicted values for TPC under the optimised conditions for 80% methanol and 80% ethanol were 16.5 and15.8 mg GAE/100 g DW, respectively. The results obtained from this study demonstrate that Cosmos caudatus can be used as a potential source of antioxidants for food and medicinal applications.